2005
DOI: 10.1103/physrevlett.95.080505
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Subspaces Having No Bases Distinguishable by Local Operations and Classical Communication

Abstract: It is proved that there exist subspaces of bipartite tensor product spaces that have no orthonormal bases that can be perfectly distinguished by means of LOCC protocols. A corollary of this fact is that there exist quantum channels having sub-optimal classical capacity even when the receiver may communicate classically with a third party that represents the channel's environment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
72
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 13 publications
(21 reference statements)
3
72
0
Order By: Relevance
“…Thus it follows from Theorem 1 that any basis for S is unambiguously distinguishable by LOCC. Interestingly, recently Watrous found another kind of special bipartite subspace having no basis exactly distinguishable by LOCC [14].…”
mentioning
confidence: 99%
“…Thus it follows from Theorem 1 that any basis for S is unambiguously distinguishable by LOCC. Interestingly, recently Watrous found another kind of special bipartite subspace having no basis exactly distinguishable by LOCC [14].…”
mentioning
confidence: 99%
“…Local distinguishability of a finite set of orthogonal multipartite states has become an increasingly interesting topic in quantum information partly due to its important applications in classical data hiding [1] and quantum channel capacity [2][3][4][5]. It is well known that orthogonal quantum states can always be perfectly distinguished if there are no restrictions on the measurements one can perform on the system.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005 Watrous demonstrated that there exists a class of m ⊗ m subspaces having no orthonormal bases locally distinguishable if m > 2 [4]. Such subspaces are said to be locally indistinguishable; otherwise, they are said to be locally distinguishable.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of restrictions on the measurement on the ability to discriminate-either ambiguously or unambiguously-between quantum states has also recently attracted much attention. In particular, the limits of LOCC discrimination have been investigated in [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], for instance. Such limits are at the base of the existence of hiding states [34][35][36][37], which are orthogonal and therefore perfectly distinguishable by global operations, but hardly distinguishable by LOCC measurements.…”
Section: Introductionmentioning
confidence: 99%